The Effect of the Removal of User Fees for Delivery at Public Health Facilities on Institutional Delivery in Urban Kenya - Calhoun, Lisa M. (Matern Child Health J, 2017)
Objectives In 2013, Kenya removed delivery fees at public health facilities in an effort to promote equity in access to health services and address high maternal mortality. This study determines the effect of the policy to remove user fees on institutional delivery in a population-based sample of women from urban Kenya. Methods Longitudinal data were collected from a representative sample of 8500 women from five cities in Kenya in 2010 with a follow-up interview in 2014 (response rate 58.9%). Respondents were asked about their most recent birth since 2008 at baseline and 2012 at endline, including the delivery location. Multinomial logistic regression is used, controlling for the temporal time trend and background characteristics, to determine if births which occurred after the national policy change were more likely to occur at a public facility than at home or a private facility. Results Multivariate findings show that women were significantly more likely to deliver at a public facility as compared to a private facility after the policy. Among the poor, the results show that poor women were significantly more likely to deliver in a public facility compared to home or a private facility after policy change. Conclusions for Practice These findings show Kenya’s progress towards achieving universal access to delivery services and meeting its national development targets. The removal of delivery fees in the public sector is leading to increased use of facilities for delivery among the urban poor; this is an important first step in reducing maternal death.